Gender Role Optimization in Child Protection To Prepare Gold Generations - Titik Haryati (ADI Publisher, 2020)
The golden generation as the nation's next generation has a strong and strong character for development and national resilience so that parenting in the family involves father and mother as parents and primary educators are also the first in child development as an effort preparing a golden generation requires gender equality and partnerships in families through family management that is physically and mentally healthy. The family as a small community organization has an important role in facilitating and responsible for child development. Fulfilling the basic needs of education and health and welfare is a form of mastery of knowledge and skills through informal education provided by parents. Awareness of education for parents is a priority to increase gender roles, setting up a golden generation. Parents are fathers and mothers who are in an organization small communities use family management to provide child protection by not distinguishing the roles of women and men as responsibilities for children in order to be a golden generation and quality. By nature women give birth so that women as a mother is the person closest to the child because during pregnancy the mother interacts with the child. The child will interact with the mother while in the womb until the process of later birth in childhood and adolescence and even old age. Father as a man inside The household is the leader of the family and the priest in the family has responsibilities economically and with family needs so that the partnership between father and mother is a requirement in family management in creating a healthy family harmony and rochani. Law Number 35 Year 2014 Article 20 reads: “State, Government, Government Region, Community, Family, and Parents or Guardians are obliged and responsible for The 1945 Constitution, articles 27 and 28B, so that gender roles can be optimal and children are ready to be the golden generation.